Developing Interactive Teaching Materials for Practical Webinar Tutorials in Distance Education - Gafur, Abd; Suryo Prabowo (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
Interactive teaching materials play an important role in distance learning by presenting various media formats such as text, audio, and video to facilitate effective learning. This study aims to develop interactive teaching materials and test their feasibility and practicality in supporting the implementation of distance learning. The research used the research and development method in accordance with Sugiyono’s development model. Research data were obtained from material and media experts, tutors, and document analysis. The instruments used were trial and interview assessment sheets. The collected data were analyzed using descriptive statistics. The results of the study show that the developed product was deemed feasible by both material and media experts and was proven practical through trials with tutors. These findings indicate that these materials are feasible and practical to support webinar-based tutorials. This study contributes to the field by developing integrated teaching materials that strengthen tutors’ pedagogical and technical competencies in conducting practical-course webinar tutorials within open and distance higher education.